Lomustine's nanoemulsion as nose-to-brain drug delivery system for CNS tumor treatment - Maryam H. Alaayedi; Nidhal K. Maraie (Elsevier, 2023)
Nose-to-brain delivery allows the direct targeting of drug molecules bypassing the Blood Brain Barrier and systemic effect. Nanoemulsion is one of the novel strategies to deliver drug in this route due to its simplicity in manufacturing, long-term stability, and strong solubilization property for drug. The anticancer drug lomustine had poor oral bioavailability in addition to its serious side effect, therefore, developing more effective drug delivery with direct targeting towards the brain through intra-nasal administration applying nanoemulsion technology is a promising alternative. The work involved lomustine solubility screening in oils, surfactants and cosurfactants as well as emulsifier ratio (Smix) nanoemulsion area was identified using pseudo-ternary phase diagrams. Eighteen nanoemulsion formulas were produced for optimization, then characterized for droplet size, polydispersity index, zeta potential, entrapment efficiency, conductivity, transmittance, dilution, visual transparency, physical stability and in vitro release. The optimum NE formula showed droplet size, zeta potential, polydispersity index, entrapment efficiency, %transmittance, conductivity of 31.31 nm, −30.65 mV, 0.159, 98.12%, 99.08%, and 951 us/cm, respectively. The best formula released 100% lomustine within 15 min which is a promising potential drug delivery system that may deliver the drug quickly and directly to the brain as a safe and effective alternative to oral delivery.